Biopsychosocial factors and global perceived effect scale on the subject with chronic pain: an analytic cross-sectional study - Roque, Graziella Cristina; Antonio, Tiago Tsunoda del; Jassi, Fabrício José; Chaves, Thais Cristina (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Background: Chronic pain is an emotional and sensorial experience that triggers functional incapacity guided especially by the biopsychosocial changes, that lead to its aggravation directly affecting the recovery of the patient. Objective: To verify the presence of biopsychosocial factors in the subject with chronic pain on the physiotherapeutic care undergone in a clinical physiotherapy school. Method: A cross-sectional study, conducted in the physiotherapy clinic of the Health Sciences Center of the Universidade Estadual do Norte do Paraná, in which were evaluated 26 subjects with chronic pain through the Pain Numerical Rating Scale; Hospital Anxiety and Depression Scale; Pain Catastrophizing Scale; Fear Avoidance Beliefs Questionnaire; and Global Perceived Effect Scale. The statistical analysis had significance value of P≤0.05. Results: Even with reduction of pain intensity with P=0.04, the values do not indicate clinically relevant difference. The global perceived effect scale does not indicate a significant improvement of the subjects; however this is justified because the treatment does not address biopsychosocial aspects, being a technical approach. Conclusion: The treatment of chronic pain associated with a biopsychosocial approach would be the most indicated in clinical practice.